Severe malaria in adolescents in the post-COVID-19 era, at the university hospital of Libreville - Mintoo, Steeve; Loembe, Fifi C.; Mpira, Sylvie; Koko, Jean; Ategbo, Simon J. (International Journal of Contemporary Pediatrics, 2024)
Background: Malaria is a parasitic, life-threatening, vector-borne disease that is a significant public health problem in sub-Saharan Africa. The disorganization of health systems characterized the COVID-19 pandemic period. We aimed to assess the impact of these induced changes on adolescent malaria. Methods: We conducted a longitudinal study during the 2021 year in our pediatric ward. We enrolled all patients treated for malaria based on a positive thick smear and rapid diagnostic test for malaria. We noted the age, the delay to consultation, the signs at admission, the haemogram test, the parasites count, and the duration of stay. Results: Of 1734 inpatients, 689 (39.7% (95% CI [37.4%-42%]) were for malaria, including 128 adolescents. We rated 417 (24.3%; 95% CI [22.3%-26.3%]) cases of severe malaria, including 94 (73.4%; 95% IC [65.8-81.1%]) adolescents. The median delay to consultation for adolescents was 2 days vs children 3 days p=0.004. Admission signs were leads by fever (98%), prostration (38%) and pallor (32%). The median length of hospital stay for adolescents was 3 days vs children 4 days (p=0.0263). Adolescent status was associated with more severe forms (OR=2.04 95% CI [1.33-3.13]) and more cerebral forms (OR=3.8 95% CI [2.6-5.6]). Conclusions: The post-COVID-19 era was marked by a higher incidence of malaria and severe forms in adolescents, primarily cerebral malaria. Due to potential sequelae, they need a follow-up to estimate the real aftermaths of the pandemic on the children population.